Care coordination for people with complex care needs in the U.S.: A policy analysis. (September 2014) - Martyn, Harriet; Davis, Karen
The U.S. boomer population reaching the age of Medicare eligibility and the rising cost of healthcare are putting pressure on the sustainability of the federal Medicare fund. As a result people over 65 with complex care needs risk spending more out of pocket on their healthcare or becoming eligible for Medicaid as their personal resources are depleted. A number of recent initiatives have been developed to improve coordination of care for Medicare beneficiaries with complex care needs and to address the disjointed provision of care for patients who are eligible for Medicare and Medicaid. In order to improve care and reduce the financial burden on patients with complex care needs in the U.S., policy makers must take a system-wide approach, strengthening primary care systems, tackling those at highest risk, increasing care at home and in the community instead of institutions, ensuring better financial protection for patients, and offering healthcare providers financial incentives.